Survival of GRAS base formulated vaccine against environmental stress and storage durability - Shamsudin, Mariana Nor; Idrus, E. S.; Abdul Rahim, R.; Idris, N. H.; Mohd Alipiah, N. F. (2012)
Current study explores the rigidity and endurance of GRAS base formulated vaccine against environmental stress exposed during process of formulation, packaging and its release into desired pathway and environment. Evaluation were conducted from initial step in vaccine formulation, freeze drying process preservation, storage endurance, packaging environment until exposure into gut environment. Experiment were designed to suit bile condition of fish stomach to ensure viability of vaccine after passing through the fish intestine and time taken for the vaccine to be release and circulated in the bloodstream. Salinity reading tested ranged between 5ppm – 35ppm and pH reading recorded for test ranged between pH2 (acidic bile condition) to pH10 (alkaline). Experiments were conducted for the duration of 24 months for shelf life storage.